Science and the Navy : the History of the Office of Naval Research. - Sapolsky, Harvey M. (Princeton University Press, 2014)
Addressing all those interested in the history of American science and concerned with its future, a leading scholar of public policy explains how and why the Office of Naval Research became the first federal agency to support a wide range of scientific work in universities. Harvey Sapolsky shows that the ONR functioned as a ""surrogate national science foundation"" between 1946 and 1950 and argues that its activities emerged not from any particularly enlightened position but largely from a bureaucratic accident. Once involved with basic research, however, the ONR challenged a Navy skeptical.
Cover; Contents.
Keywords: United States. -- Office of Naval Research -- History.; United States. -- Office of Naval Research; Science and state -- United States -- History.; Federal aid to research -- United States -- History.; Politique scientifique et technique -- États-Unis -- Histoire.; HISTORY -- United States -- 20th Century.; TECHNOLOGY & ENGINEERING -- Marine & Naval.; TECHNOLOGY & ENGINEERING -- Military Science.; Federal aid to research; Science and state; United States; History